The Sexual State Sexuality and Scottish Governance 1950-80 - Davidson, Roger (Edinburgh University Press, 2022)
How did the Scottish government respond to sexual attitudes and behaviour in the period 1950 to 1980?GBS_insertPreviewButtonPopup(['ISBN:9780748645602','ISBN:9780748649433']);'In this ground-breaking book, Roger Davidson and Gayle Davis examine sexualities and their relation to, and their shaping through, interplay with governance in Scotland in the post-war era up to the administration of Margaret Thatcher. This largely untold and fascinating history not only illuminates a significant lacuna in Scots contemporary history, but also brings considerable nuance and regional comparative element to the now burgeoning scholarship of the contemporary history of sexuality in Britain. ...